The Impact of Lecture Involvement in the Mathematics Learning Process on Student Satisfaction - Aini, Kuratul; Mahsup, Mahsup; Mandailina, Vera; Febriani, Putri Ayu; Syaharuddin, Syaharuddin (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
The main focus of this study revolves around the dimension of faculty involvement, encompassing direct interaction, support, and guidance within the context of mathematics instruction, vis-à-vis student satisfaction. This research adopts a quantitative approach employing a survey methodology aimed at exploring the impact of faculty involvement in the mathematics leraning process on student satisfaction levels. The respondents consist of 13 male and 31 female students. The research instrument utilized is a questionnaire comprising 10 questions, employing a Likert scale ranging from strongly disagree (score 1) to strongly agree (score 5). Indicators within the questionnaire cover various aspects such as the clarity of instructional materials, information related to recent developments in the field of mathematics, and support in overcoming learning difficulties. Data analysis for this research utilizes descriptive statistics and the student's t-test with the assistance of the JASP software. The criterion for drawing conclusions is if the Sig value < 0.05, then H0 is rejected, indicating a significant influence of lecturer involvement on student satisfaction. The results of the hypothesis test using the paired sample T-Test show a t-test value of 0.106 with a p-value of 0.917. The interpretation of the hypothesis test results supports the null hypothesis (H0), stating the absence of differences in the perceptions of male and female students regarding lecturer involvement in teaching mathematics and its impact on student satisfaction. With a high p-value of 0.917, indicating homogeneity in perceptions, further research is recommended to explore factors that may influence students' perceptions of lecturer involvement. The conclusion of this study is expected to provide in-depth insights into the relationship between lecturer involvement and student satisfaction, laying the groundwork for efforts to enhance the quality of mathematics education at the university level.